Perbandingan akurasi diagnostik kriteria cornell product dengan kriteria sokolow lyon dalam menentukan hipertrofi ventrikel kiri pada pasien hipertensi obese di RSUP H. Adam Malik, Medan - Muhammad Azhari; Rahmad Isnanta; Zainal Safri; Refli Hasan (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction : LVH is an important cardiovascular risk factors in hypertensive patients.Accuracy of ECG criterias was relatively low in diagnosis LVH. Cornell product criteria are the criteria used in the diagnosis LVH in obesity because of easier application. The aim of this study was Determine the accuracy of the Cornell product and sokolow lyon in the detection of left ventricular hypertrophy in obese hypertensive patients at Adam Malik General Hospital.Methods : This cross sectional study from September to October 2015 on 61 cardiology policlinic patients and we did anamnesis, measurement of blood pressure, height, body weight, BMI, BSA, ECG and Echocardiography.Result : From61 patients admitted to cardiology policlinic, we found 34 male and 27 female. The result of echocardiography revealed 38 of hypertensive patients have LVH (62.3%). Sensitivity, specifity and accuracy of different ECG criteria for diagnosis LVH ranged from 31.6% (Cornell product and Romhilt estes) to 47.4% (Cornell Voltage), 65.2%(Cornell Voltage) to 95.8%(Sokolow Lyon), 50% (Cornell Product and Romhilt Estes)to 61.7% (Sokolow Lyon). Positive predictive value were ranged from 75% (Cornell & Romhilt Estes) to 92.9% (Sokolow Lyon) andNegative predictive value were ranged from 42.2%(Cornell Product and Romhilt estes) to 46.8% (Sokolow lyon).Conclusion :The accuracy of ECG criteria Cornell Product no better than lyon Sokolow criteria in terms of assessing LV hypertrophy in hypertensive patients with obesity.Key word : Leftventricular hypertrophy, Cornel product, sokolow lyon, hypertensive obese